Analysis of the Judge's Decision in the Case of Isbat Nikkah for Husbands Who Have Passed Away (Study of Decision Number: 409/Pdt.G/2023/Pa.Plk) - Ahmad Suwardi; Mulida Hayati; Nuraliah Ali (Green Publisher Indonesia, 2025)
This study discusses the analysis of the judge's decision regarding isbat nikah for husbands who have passed away, especially in Case Number: 409/Pdt.G/2023/PA.Plk. Isbat nikah is an important legal process to provide certainty of legal status, especially for couples who do not have a marriage certificate. This study aims to understand the judge's considerations in deciding the case and its implications for inheritance rights and civil administration. The method used is normative juridical research, which examines laws and regulations and court practice. The results of the study show that judges consider legal certainty and the interests of the parties in their decisions, which aims to protect the rights of the families left behind. In addition, the analysis shows the importance of marriage registration to avoid legal disputes in the future. These findings are expected to contribute to the development of marriage law and the protection of women's rights in the context of Islamic law in Indonesia.